DISORDER OF FUNCTIONAL STATE OF RESPIRATORY SYSTEM AS A RISK FACTOR IN EMPLOYEES OF SULFATE CELLULOSE PRODUCTION - N. M. Meshchakova; V. S. Rukavishnikov (Acta Biomedica Scientifica)
The functional state of respiratory system, was studied in the employees of sulfate cellulose production, exposed, to the harmful chemical substances — methylsulfuric compounds (MSC), chlorine and chlorodioxide, the lime dust and. the alkaline aerosol. It was found, that the significant disorder prevalence of the external breathing function increasing as the occupational work length, increases and. manifestating as the moderate decrease in the main indices of the pulmonary ventilation, was observed to be in the practically healthy employees exposed, to a chemical factor. The significant influence on the functional state of respiratory system, may exert the smoking effect factor exaggerating the influence of a chemical factor.